THE EFFECT OF EXERCISE PRESCRIPTION ON FORCE OUTPUT AND MUSCLE ACTIVATION DURING THE NORDIC HAMSTRING EXERCISE. Issue 4 (1st February 2017) - Buhmann, Rob; Shield, Anthony; Sims, Casey
Abstract : Background: The Nordic hamstring exercise (NHE) is employed to increase eccentric strength and reduce the risk of recurrent hamstring strain injury. Currently, the prescription of the NHE offering most benefit is unknown. Objective: To assess force production, muscle activation and kinematics during two NHE prescriptions. It was hypothesized that a 5*6 repetitions protocol would yield greater average forces, smaller force drops and greater muscle activation per set compared to a 3*10 protocol. Additionally, it was hypothesised that during both protocols, peak muscle activation would occur at shorter muscle lengths than peak force. Design: Randomised cross-over study. Setting: Recreationally trained and sub-elite male athletes. Participants: Thirteen healthy males (age 23±4 years, stature 178±6.5 cm and weight 75±17 kg). Interventions: Participants performed 3*10 and 5*6 repetitions of the NHE (on separate occasions), 3 minutes rest was given between sets. Main Outcome Measurements: Load cells were used to record knee flexor force, electromyography (EMG) was used to measure hamstring activation and a goniometer was used to measure knee flexion angles during each repetition. Results: Average force (666.44N during 3*10 vs. 697.95N during 5*6) and force drop per set (−54.48N during 3*10 and −51.73N during 5*6) was not different between protocols. Additionally, normalised biceps femoris (87 vs. 79% of max isometric EMG during 3*10 and 5*6 respectively) and medial hamstring (111 vs. 98% of max isometric EMG during 3*10 and 5*6 respectively) EMG per set was not different between protocols. For both protocols a significant difference between the angle of peak torque and angle of peak biceps femoris EMG was observed (p<.001, mean difference= 15.4, CI=13.6–17.2 degrees). Conclusions: Force output and muscle activation during the NHE is not affected by prescription. Peak activation of the biceps femoris appears to occur at shorter muscle lengths than peak force, suggesting inhibition of this muscle at long lengths.